Eco-Critical Perspective in Tamasya Danau Toba Poetry by Sitor Situmorang - Eko Putro Setiawan, Kodrat; Suwandi, Sarwiji; Winarni, Retno (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aims to describe the representation of nature, the value of caring for the environment, and an eco-critical perspective in the poem Tamasya Danau Toba. The method in this research is descriptive qualitative. The source of the data in this study is a poem entitled Tamasya Danau Toba by Sitor Situmorang. The result of this research is that Nature's Representation in the poem Tamasya Danau Toba includes dictions: mountains, water, lakes, earth, sky, rocks, lava, grass, forests, continents, fields, rice fields, and trees. The value of caring for the environment is in the form of a description of the condition of the forest that is threatened with extinction and the clearing of increasingly wide fields. The eco-critical perspective in the poem Tamasya Danau Toba is that the clearing of fields/rice fields must take into account the balance of nature in this case the forest. Millions of hectares of Indonesia's forests are damaged every year, at the beginning of the year Indonesia was hit by various disasters such as floods and landslides. Experts argue that one of the causes is the increasingly widespread conversion of forests to oil palm or rubber.